Officers And Directors (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
PRESIDENT Michael Lawrence Haider New York City PAST PRESIDENT Willis McGerald Peirce New York City VICE-PRESIDENTS 0. B. J. Fraser, New York City J. B. Morrow, Pittsburgh, Pa. J. L Gillson, Wilmington, Del. ' L F. Reinartz, Middletown, 0. Philip Kraft, New York City R. W. Thomas, Tucson, Ariz